ENGARUH KEPEMIMPINAN DAN PENGEMBANGAN KARIR TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. BANK SINARMAS, TBK CABANG MANADO - TANGKILISAN, FRENTINO; AREROS, WILLIAM AGUSTINUS; WALELENG, GRACE (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract:Leadership is needed to direct or guide others or subordinate toward the achievement of anorganizational goal. To achieve these goals, required the better human resources inside company ororganization through career development activities. Currently, the employee job satisfaction is very importantnow days because it can affect the way of the company. The purpose of this research is to examine the influenceof leadership and career development to employees’ job satisfaction at PT. Bank Sinarmas, Tbk branchManado.The method used in this research is quantitative method using logistic regression model. Thepopulation is 48, total sampling is used as sampling technique in order to obtain all 48 employees as the sample.Interviews, observation, questionnaires are used in collecting data. Analysis method is using R-Squarecoefficient, Hosmer and Lemeshow test as well as hypothesis test using EXP value or ODDS ratio and ChiSquare to measure the effect of variables using SPSS 16.0 Windows.The result shows the significant value of leadership variabel is 0,035 and career development variabelis 0,01, both variables has significant influence to job satisfaction. Furthermore, the result show that leadershipand career development has significant influence as partial and simultaneous toward job satisfaction.Keywords: Leadership, Career development, Job satisfaction